Os jornalistas, o segredo de justiça e o sigilo profissional - Cortez, Maria do Rosário Parreira Cano Barreira (2017)
The cornerstone of this dissertation is to understand whether the current legal framework of the journalists’ professional secrecy fosters violations of the judicial secrecy. For that purpose, it was taken into consideration those scenarios when an information source disseminates information to a journalist about a criminal case under judicial secrecy and publishes them through news under unnamed sources, which are covered by professional secrecy. If, on the one hand, it is certain that journalists have both legal and deontological duties as well as the right to professional secrecy, on the other hand criminal law might force them to reveal their sources of information whenever the court orders them to give evidence and breach the secrecy. Portuguese case law has been stating that the incident of the breach of the professional secrecy can only take place if the journalist has been called to the criminal process and has been heard as a witness. If he was called as a defendant, his status as well as his right to remain silent will certainly overlap the professional secrecy legal framework. The main issues here are the following: Is the information source protected and guaranteed that his identity will not be revealed? If the journalist has both the right and the duty to professional secrecy, what should he do? Does the legal framework of the journalists’ professional secrecy turns the judicial secrecy ineffective?